Poverty Environment Nexus : Sustainable Approaches to Poverty Reduction in Cambodia, Lao PDR and Vietnam - World Bank (Washington, DC, 2012)
This is a draft edition of the Poverty Environment Nexus (PEN) report for Cambodia, Lao PDR and Vietnam. The purpose of this conference edition is to present the findings from the studies that have been undertaken in each country over the last three years as well as to obtain relevant comments and feedback from the conference participants that could be included in the final edition of the report. The material presented in this report is based upon comprehensive case studies as well as national analytical work performed in each country. This second phase of the PEN study is designed to address several of the unsolved issues faced by the first phase and within the existing PEN literature on Cambodia, Lao PDR and Vietnam. Since the earlier study found that the nexus may often be identified at disaggregated, or local, levels, the analysis in the second phase of the study was conducted both at the regional, provincial and district levels for the national studies (macro-levels) and on the district, village, commune, and household levels in the (case) studies (micro-level). This combination of macro and micro approaches results in more substantive findings, which are elaborated in detail in these elaborations, may then lead to a better scope for defining policy interventions.